The nursing of 20 cases of high myopia complicated with fixed esotropia - LiXiuling; LinJing; XiaoHuiming; HeQingdong (眼科学报, 2015)
To summarize the nursing experience of 20 cases of high myopia complicated with fixed esotropia. Before surgery, psychological nursing and self-care education were necessary. After the operation, ocular symptoms and complications should be closely observed and treatment in a timely manner. Explicit instructions after discharge and telephone follow-up played a pivotal role in improving clinical efficacy, preventing complications and enhancing patients’ quality of life.